Bonded body of a base material and a metal layer

CN114270483BActive Publication Date: 2026-10-13WORLD METAL KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080048338.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-08
Filing Date
2020-04-03
Publication Date
2026-10-13
Estimated Expiration
2040-04-03

AI Technical Summary

Technical Problem

[0010](1)陶瓷与金属皮膜间的贴紧较弱

Benefits of technology

[0063]本发明在接合底材的接合部表面上形成中间层的覆盖膜,做成借由该中间层覆盖膜接合金属层的构造,该中间层覆盖膜的构造为在中间层覆盖膜中埋入有形成通过锚定效果接合金属层的锚的锚形成物,由此牢固地接合于熔接层而分散的构造,中间层覆盖膜熔接于接合底材的接合部表面,锚形成物的顶端从中间层覆盖膜向外突出的构造,因此在与金属层发生接合时,金属皮膜接合于中间层覆盖膜的表面及锚形成物的突出部这双方,所以通过锚定效果被接合的金属层相对于其接合底材得到极高的贴紧力,另外该贴紧力的偏差也较小。而且,实施接合时也不需要高价的设备,能够以较低成本的费用实现接合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114270483B_ABST
    Figure CN114270483B_ABST
Patent Text Reader

Abstract

The present application provides a kind of bonding body for bonding substrate and metal layer, when the metal layer is bonded to the bonding substrate, the metal layer has stronger close force, the deviation of close force is also smaller, and bonding can be realized at lower cost.I.e., the bonding body of the present application for bonding substrate (1) and metal layer (5) by covering film (2) of intermediate layer formed on the bonding surface of bonding substrate (1) to bond metal layer (5) to bonding substrate (2), covering film (2) of intermediate layer is fused to the bonding surface of bonding substrate (1), while the anchor formation (3) for bonding metal layer (5) by anchoring effect is dispersedly embedded in covering film (2) of intermediate layer, part of anchor formation (3) protrudes outward from covering film (2) of intermediate layer, while being fused to covering film (2) of intermediate layer, metal layer (5) is bonded to the surface of covering film (2) of intermediate layer and the surface of anchor formation (3) protruding outward from covering film (2) of intermediate layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a bonding body for a bonding substrate and a metal layer, and more specifically, to a bonding body for a bonding substrate and a metal layer having a strong adhesion bonded to the surface of the bonding substrate. Background Technology

[0002] As a prior art for bonding a metal layer to a substrate such as ceramics, a metal that is diffusive to ceramics is sprayed onto the surface of a ceramic plate, such as Ti or Cr metal, and then Cu is further deposited on it, and then a metal layer is formed on it by applying a plating or the like. Although such a technology is well known, there are other technologies, such as the inventions described in Patent Documents 1 to 7.

[0003] The invention described in Patent Documents 1 and 2 is a method in which a copper plate is pressed onto an alumina ceramic plate and then joined together after the copper plate is heated to near its melting point in a vacuum.

[0004] The invention described in Patent Document 3 is a method in which active metal (Ag-Cu-Ti) powder is coated or a thin sheet is sandwiched between a ceramic plate and a copper plate, and then pressure, heat and join them in a vacuum.

[0005] The invention described in Patent Document 4 is a method in which an alumina ceramic material is immersed in a molten salt bath of NaOH alone or NaOH+KOH, and after the surface is excessively roughened, a metal layer is formed by applying an electroless plating layer or a metal plating layer.

[0006] The invention described in Patent Document 5 is a method (HTCC) in which W, Cu-W, and Mo-Mn pastes are printed on a ceramic plate, then sintered at high temperature in a reducing environment, and then a metal layer is formed by applying a plating or the like.

[0007] The invention described in Patent Document 6 is a method (LTCC) in which Ag, Ag-Pd, and Cu pastes are printed and sintered on glass-like ceramics, and then a metal layer is formed by performing plating or the like.

[0008] The invention described in Patent Document 7 is a method in which a Ti-containing coating is formed on a ceramic, and then the Ti in the coating is diffused into the ceramic by heat treatment to obtain adhesion.

[0009] The prior art of bonding metal films onto the aforementioned ceramic or other substrates has the following problems.

[0010] (1) The adhesion between the ceramic and the metal film is relatively weak. (2) There is a large deviation in the adhesion force. (3) The cost of joining is relatively high. (4) The technical difficulty of bonding the cover film is very high. (5) Covering film bonding requires expensive equipment.

[0011] Patent documents Patent Document 1: Specification of US Patent No. 3766634 Patent Document 2: Specification of US Patent No. 3994430 Patent Document 3: Japanese Patent Application Publication No. 1-181499 Patent Document 4: Japanese Patent Application Publication No. 3-2833 Patent Document 5: Japanese Patent Application Publication No. 61-58296 Patent Document 6: Japanese Patent Application Publication No. 61-170094 Patent Document 7: Japanese Patent No. 2778143 Summary of the Invention

[0012] The present invention is based on the following problem: to provide a bonding body for bonding a substrate and a metal layer, wherein when the metal layer is bonded to the bonding substrate, the metal layer has a strong adhesion force and a small deviation in the adhesion force, and the bonding can be achieved at a low cost.

[0013] This invention relates to a bonding body for a substrate and a metal layer, wherein the metal layer is bonded to the bonding surface of the substrate via an intermediate cover film. The invention is characterized by anchor formations embedded in the intermediate cover film, while the intermediate cover film is fused to the bonding surface of the substrate. The anchors bond the metal layer through an anchoring effect. A portion of the embedded anchor formations protrudes outward from the intermediate cover film and is fused to it. The metal layer is bonded to both the surface of the intermediate cover film and the surface of the anchor formations protruding outward from the intermediate cover film.

[0014] In this invention, the bonding substrate can appropriately use Al2O3, AlN, Si3N4, BN, SiC, ZrC, WC, DLC, diamond, silicon wafer, sapphire, ceramics, porcelain, GaC, GaAs, GaN, GaO, LED, graphite, etc. In addition, all materials can be used as substrate materials for electronic components, as long as they are not used in the heat treatment that melts the intermediate layer cover film of this invention.

[0015] The shape of the bonding substrate can be any of the following: plate-shaped, column-shaped, spherical, cylindrical, or rod-shaped, and is not limited to a specific shape.

[0016] The intermediate layer cover film is composed of one or more metal components selected from Fe, Ni, Co, Sn, Cu, Ag, Au, Ti, V, Zr, Nb, Ta, W, Mo, Mn, B, Zn, Al, In, Tl, Se, Ir, Pd, Pb, Sb, As, Y, Nd, Te, Ge, Si, alkali metals, and alkaline earth metals, or compounds of such metal components, which are melted to form a glassy oxide, and is fused to the bonding substrate.

[0017] When welding the interlayer cover film, the bonding substrate and anchoring form must naturally be in a solid state, and the melting point of the interlayer cover film must naturally be below the melting point of the bonding substrate and anchoring form.

[0018] The intermediate layer cover film is not just a layer composed of oxides. Rather, as long as the material has excellent compatibility with oxides, ceramic components such as nitrides, carbides, borides, silicides, and sulfides, as well as metal components and metal compound components can coexist as needed.

[0019] A welding agent containing a mixed and dispersed anchoring agent is applied to the joint surface of the bonding substrate, and then heated and welded to form an intermediate layer cover film.

[0020] The welding agent consists of a coating liquid and an anchoring agent dispersed in the coating liquid. The coating liquid contains or is mixed with or dissolved metallic components or compounds of the same metallic components selected from Fe, Ni, Co, Sn, Cu, Ag, Au, Ti, V, Zr, Nb, Ta, W, Mo, Mn, B, Zn, Al, In, Tl, Se, Ir, Pd, Pb, Sb, As, Y, Nd, Te, Ge, Si, alkali metals, and alkaline earth metals. In addition, tackifiers such as cellulose nitrate are added as needed to improve the coatability of the coating liquid.

[0021] An anchor forming an anchor that bonds the metal layer through an anchoring effect may be made of ceramic or metal particles or fibers selected from oxide powder, carbide powder, nitride powder, boride powder, silica powder, diatomaceous earth powder, silica gel powder, glass powder, diamond powder, DLC powder, ceramic powder, porcelain powder, silica fiber powder, ceramic fiber, mica powder, graphite powder, kaolin powder, metal powder, metal fiber, metal whiskers, etc., one of these can be used alone or two or more can be used in combination as needed.

[0022] The anchor form of the present invention is not limited to a specific shape. Before the anchor form is embedded in the intermediate cover film and dispersed and welded, its shape can be spherical, angular, polygonal, or fibrous. The anchor form embedded in the intermediate cover film and dispersed and welded can also be in the form of overlapping anchor forms or anchor forms overlapping to form a mesh shape.

[0023] In particular, when the mesh shape forms a primary metal layer after heating and welding, the primary metal layer fills the gaps in the mesh, thus dramatically increasing the bonding strength.

[0024] To reduce the welding temperature of the intermediate layer cover film, various metal salts, metal oxides and their salts can be used in part or all of the welding agent coating solution.

[0025] That is, metal salts, metal oxides and their salts may be used in part or all of the metal components or compound components of Fe, Ni, Co, Sn, Cu, Ag, Au, Ti, V, Zr, Nb, Ta, W, Mo, Mn, B, Zn, Al, In, Tl, Se, Ir, Pd, Pb, Sb, As, Y, Nd, Te, Ge, Si, alkali metals, alkaline earth metals.

[0026] Metal salts, metal oxides and their salts, such as tin sulfate, copper sulfate, vanadium sulfate, calcium chloride, tungstate, boric acid, borate, silicate, molybdate, etc., can be used.

[0027] In this invention, while the weld layer, which will become the intermediate cover film, is firmly welded to the ceramic substrate, the anchor formation also needs to be firmly bonded to the weld layer at the same time. For this purpose, the most suitable welding agent composition and the most suitable anchor formation material need to be selected for each ceramic substrate. That is, the most suitable welding conditions need to be selected, including the composition of the welding agent, the thickness of the weld layer, and the type, shape, mixing ratio, welding temperature, and time of the anchor formed by the welding.

[0028] The relationship between the ceramic substrate, the welding agent, and the anchor formed by welding is such that, for example, when the ceramic substrate is alumina ceramic, the anchor formed is preferably alumina particles.

[0029] The welding agent can be a mixture of tungstate, vanadium sulfate, boric acid, etc. The welding conditions are as follows: Vanadium sulfate is decomposed into V₂O₃ at 1100°C in atmospheric heat, then melted at 690°C; boric acid is oxidized to B₂O₃, then melted at 577°C; and tungstate is also oxidized to W₂O₅, lowering its melting point. These three substances react with each other and are then welded together with alumina particles onto the alumina substrate at 1100°C. On the other hand, since the melting point of the alumina particles in the anchor formation is 1600°C, they will not melt or change shape at this welding temperature, thus achieving welding.

[0030] When the ceramic substrate is AlN ceramic, the anchoring material can be BN particles. When the ceramic substrate is SiC ceramic, SiC, WC, and ZrC particles are suitable for anchoring, as they have strong adhesion to the substrate.

[0031] When the anchor-formed material is a true sphere of SiO2 with an average particle size of about 1 μm, and the addition amount is 50 g / L, the appearance of the anchor-formed material after the formation of the primary metal layer is as follows: Figure 2 The situation shown. Figure 2 In the diagram, the white dots are anchor formations, surrounded by a primary metal layer. The anchor formations are fused together while remaining separate from each other, creating numerous gaps between them. The non-electrolytic plating metal of the primary metal layer is applied to fill these gaps, while the protrusions of the anchor formations are also surrounded and covered. The gaps between the anchor formations are filled and the protrusions of the anchor formations are covered, and the strong adhesion of the invention is believed to be generated by the anchoring effect of the continuous electroless plating layer.

[0032] On the other hand, when the amount of SiO2 particles added is small (below 10 g / L), the anchoring material is scattered and becomes an accumulation of overlapping anchoring materials or a flattened surface with fewer gaps. It does not become a so-called three-dimensional structure. Therefore, the adhesion is slightly weaker compared to when the amount added is large (above 50 g / L).

[0033] Regarding the improvement of adhesion strength, it is certainly important to appropriately add anchoring elements, but even more important is the shape of the anchoring elements. Compared with a true sphere, when polygonal shapes or linear, mesh-like, or fibrous anchoring elements are combined to form a three-dimensional structure, there is a tendency for further improvement in adhesion strength.

[0034] The size of the anchor formation and the thickness of the weld layer are determined by the required thickness of the metal layer. For example, when the required thickness of the metal layer is 2 to 5 mm (2000 to 5000 μm), it is preferable that the size of the anchor formation is 100 to 500 μm and the thickness of the weld layer is 30 to 200 μm. On the other hand, when the required thickness of the metal layer is 20 to 30 μm, a suitable size of the anchor formation is 0.5 to 5 μm and the thickness of the weld layer is 0.2 to 2.0 μm.

[0035] The thickness of the welded layer should be about 1 / 3 to 1 / 2 of the anchor form. If the welded layer is too thick, the anchor form will be buried, and the anchoring effect will be reduced.

[0036] There are several methods for applying a welding agent containing anchoring elements to a ceramic substrate. For example, there are spraying, dipping, roller coating, spin coating, spraying, and brush coating. Spraying is the best method for mass production. The most important part of the coating process is to evenly coat the anchoring material onto the entire surface and then weld it together. The coating and welding process can be repeated multiple times.

[0037] When a metal layer forms a precise pattern with a width of several micrometers, if there are areas with extremely low adhesion, the semiconductor component will peel off from the substrate after soldering, significantly reducing reliability and rendering it unusable. Therefore, the coating process is the most important process in this invention.

[0038] As for the conditions during sintering, an atmospheric environment is sufficient. Furthermore, heating can also be carried out in N2, Ar, N2+H2, or a vacuum, depending on the requirements.

[0039] The sintering temperature is determined by the relationship between the anchoring material and the welding agent. The preferred anchoring material is an oxide, carbide, boride, or nitride with a high melting point, preferably above 1500°C.

[0040] The melting point of the welded layer that forms the intermediate cover film varies depending on the composition or blending ratio.

[0041] In the welding process, the temperature and time are set in advance through a program. For example, processes such as maintaining a temperature of 300°C for 2 hours, 300-600°C for 1 hour, 600-1000°C for 1 hour, and 1000-1200°C for 2 hours, followed by slow cooling, can be pre-programmed and implemented.

[0042] When primary and secondary metal layers are formed as metal layers, small bumps or irregularities may appear on the surface due to the influence of anchoring agents. In this case, the surface can be smoothed by grinding before replating.

[0043] Importantly, the melting point of the anchor form is significantly higher than that of the weldment. If there is little difference between the melting points of the anchor form and the weldment, there is a risk that the anchor form may change shape or dissolve, resulting in reduced adhesion strength. The composition and mixing ratio of the anchor form and the preferred weldment are as described in the examples.

[0044] The types and proportions of welding agents basically need to be formulated as follows: the welding agent changes into an oxide when heated, and then melts into a glassy state, which is then fused to the ceramic substrate. Furthermore, by mixing several welding agents, a composition is made that lowers the welding temperature.

[0045] The preferred structure of the metal layer is as follows: a primary metal layer is formed on the surface of the bonding member using a wet or dry method, and a secondary metal layer is further formed on the primary metal layer using a method different from that used for the primary metal layer. Although it is not impossible to form a thicker metal layer using only a primary metal layer, there are problems such as the precipitation requiring a long time and the physical properties of the coating film being less than ideal. Therefore, it is preferable to form a structure in which the secondary metal layer is formed on the primary metal layer using other methods.

[0046] Electroplating is the most suitable method for secondary metal layers. The preferred electroplating method is copper sulfate plating, which can produce a thicker metal layer in a short time. Furthermore, the metal layer possesses excellent physical properties (ductility, conductivity), allowing for easy formation of circuits or connectors (butts) through etching or other methods. Additionally, heat treatment at 350–550°C for 30–90 minutes after plating can improve adhesion.

[0047] The reason for needing a primary metal layer is, as mentioned above, to ensure adhesion by reliably plating the gaps of the anchor formation and surrounding the anchor formation with the plating metal, while also imparting conductivity for subsequent electroplating (secondary metal layer).

[0048] Wet and dry methods can be used to form the primary metal layer, but wet methods are more advantageous when considering cost or mass production.

[0049] The wet process for the primary metal layer involves treating the metal layer with sensitizers and activators using known methods to induce the deposition of an electroless coating film. Electroless copper, electroless nickel, and electroless cobalt coatings are particularly suitable for this process.

[0050] Dry methods include vacuum evaporation, sputtering, ion plating, and CVD. Preferred methods include first depositing Cr to a thickness of 0.1–1.0 μm, followed by depositing Cu to a thickness of 0.1–1.0 μm, or depositing Ti to a thickness of 0.1–1.0 μm, followed by depositing Cu to a thickness of 0.1–1.0 μm.

[0051] The metal used for the primary metal layer is suitable for any one or more metals or alloys selected from Cu, Ni, Co, Cr, Ti, Fe, Mo, Mn, As, Au, Pd, Pt, Sn, Zn, Ni-P, Ni-B, Ni-BW, Ni-PW, Ni-PWB, Ni-Co, Ni-Co-Fe, Ni-Co-P, Co-P, Co-B, Ni-B-Mo, Co-PW, Co-P-Mo, and Fe-Ni.

[0052] The thickness of the primary metal layer is suitable to be 0.001–10 μm.

[0053] Electroless nickel and cobalt coatings can appropriately use non-electrolytic plating metals such as Ni-P, Ni-B, Ni-BW, Ni-PW, Ni-PWB, Ni-Co, Ni-Co-Fe, Ni-Co-P, Co-P, Co-B, Ni-B-Mo, Co-PW, and Co-P-Mo.

[0054] The primary application of this invention is as a heat sink for power transistors or LEDs, which requires the formation of circuits or connectors.

[0055] At this point, the bonding substrate is replaced with a ceramic substrate, and photolithography is performed on the metal layer. That is, by simultaneously performing masking and etching operations on the metal layer, circuit parts and connector parts can be formed on the ceramic substrate.

[0056] There are three representative methods for forming circuits or connectors using photolithography. A method of forming a metal layer on the entire surface of a ceramic substrate, followed by forming circuits or connectors using photolithography. A method of providing an opening in a portion of a ceramic substrate that will become a circuit or connector, applying a welding agent containing an anchor formation to the opening, and forming a metal layer only in that portion. The SAP method involves forming a 2-3 μm thick metal layer on the entire surface, attaching a dry film, and using photolithography to form openings in the circuit or connector area. A thicker plating layer is then applied to the openings. After the resist is removed, the metal layer outside the openings is removed by etching or other methods to form the connector or circuit.

[0057] The specific methods for applying the three representative methods of forming the circuit or connector to the present invention are as follows.

[0058] First Method After forming a primary metal layer on the ceramic substrate, a mask is formed by photolithography. A secondary metal layer is then applied to the portion of the metal layer corresponding to the circuit section and the connector section. After removing the mask, the primary metal layer remaining under the mask is removed, thereby forming the circuit section and the connector section (SAP method).

[0059] Second method A method for forming the circuit section and the connector section by applying a mask to the portion of the ceramic substrate other than the circuit section and the connector section, and forming primary and secondary metal layers only on the portion corresponding to the circuit section and the connector section.

[0060] Third method A method for forming circuit sections and connector sections by forming a primary metal layer and a secondary metal layer on a ceramic substrate, then forming a mask, leaving only the portions of the metal layers that correspond to the circuit section and connector section, and removing the other portions.

[0061] For the secondary metal layer surface of the circuit section and the connector section, it is preferable to implement Ni, Sn, Pd, Ag, Au, Pt, Pb, Ni-Pd-Au, Ni-Sn, Ni-Sn-Ag-Cu, Sn-Bi, Sn-Cu plating with excellent soldering and wire bonding properties in subsequent processes.

[0062] Electronic components can also be mounted on the metal layer of the present invention by bonding, as needed.

[0063] This invention forms an intermediate layer cover film on the bonding surface of a substrate, creating a structure in which a metal layer is bonded via this intermediate layer cover film. The intermediate layer cover film is constructed by embedding anchor formations within it, which act as anchors to bond the metal layer through an anchoring effect. This allows for a secure bond to the welded layer. The intermediate layer cover film is fused to the bonding surface of the substrate, and the tip of the anchor formation protrudes outward from the intermediate layer cover film. Therefore, during bonding with the metal layer, the metal film adheres to both the surface of the intermediate layer cover film and the protrusion of the anchor formation. Consequently, the metal layer bonded through the anchoring effect achieves extremely high adhesion relative to its substrate, with minimal deviation in adhesion. Furthermore, the bonding process does not require expensive equipment, enabling bonding at a lower cost. Attached Figure Description

[0064] Figure 1 It is a schematic diagram illustrating the relationship between the bonding substrate, the intermediate cover film, the anchoring structure, and the metal layers (primary metal layer and secondary metal layer). Figure 2 It is a photograph of an anchor formed on ceramic (after the formation of the primary metal layer). Symbol Explanation 1- Bonding substrate; 2- Intermediate layer cover film; 3- Anchor formation; 4- Primary metal layer; 5- Secondary metal layer. Detailed Implementation

[0065] The embodiments of the present invention will be described below in comparison with existing methods. Furthermore, these embodiments are provided for the purpose of better understanding the spirit of the invention, and therefore, the present invention is not limited to these descriptions.

[0066] Example 1 A 99% alumina ceramic plate was used as the bonding substrate. (1) The alumina ceramic plate was degreased, pickled, etched and dried using conventional methods. (2) Add water to 50g of SiO2 anchoring material with an average particle size of 0.5-1.0μm, 20g of sodium tungstate phosphate, 30g of vanadium sulfate, and 20g of boric acid to make 1L, mix for 5 hours to prepare a welding agent containing anchoring material for forming the welding layer of the intermediate layer cover film. (3) The welding agent is applied to the alumina ceramic plate of (1) by spraying. (4) It was allowed to air dry for 5 hours. (5) It was heated at 1000℃ for 2 hours using an electric furnace. (6) SiO2 particles are fused onto an alumina plate (refer to...) Figure 2). (7) In order to obtain a primary metal layer, a sensitizer and activator were applied by conventional methods to form a 2μm non-electrolytic copper plating layer. (8) In order to obtain a secondary metal layer, copper electroplating with a thickness of 30 μm was carried out using copper sulfate by conventional methods. (9) In an N2 environment, it was heat-treated at 500°C for 30 minutes. (10) A dry film is applied, and a circuit or connector is formed by photolithography. (11) After that, non-electrolytic Ni-Pd-Au plating was applied only to the portion where the semiconductor components were actually installed. (12) A heat sink for power semiconductors was fabricated. (13) The adhesion strength between the alumina ceramic plate and the copper plating was measured at three points. The peel strength is 2.5 to 2.3 kg / cm. Furthermore, if the peel strength is 1.0 kg / cm or higher, it can be used as a substrate for power semiconductors. For comparison, the fusion layer of the present invention is not formed, and the other processes are exactly the same as those of the present invention. Even with such manufacturing, the peel strength measured at the same 3 points is 0.1 to 0.05 kg / cm, which is not tight at all. It can be confirmed that this embodiment can surprisingly improve the adhesion.

[0067] Example 2 A silicon nitride substrate was used as the bonding substrate. (1) The silicon nitride substrate was degreased, pickled, etched and dried using conventional methods. Then, the surface was roughened by honing to a thickness of about Ra 0.2 μm. (2) Add water to 50g of SiC anchoring material with an average particle size of 0.5-1.5μm, 10g of CaCl2, 50g of SnSO4, 50g of TiSO4, and 50g of sodium silicate to make 1L, and stir for 5 hours to prepare a welding agent for forming the welding layer. (3) The welding agent is applied to the silicon nitride substrate of (1) by spin coating. (4) After 5 hours of natural drying, it was heated at 800℃ for 2 hours and then at 1100℃ for 2 hours. (5) SiC particles are fused onto a silicon nitride substrate. (6) In order to obtain a primary metal layer, sensitizer and activator treatments were performed using conventional methods, and a 1μm non-electrolytic Ni-B coating was applied. (7) Subsequently, in order to obtain a secondary metal layer, copper electroplating with a thickness of 50 μm was performed using a copper sulfate plating layer by conventional methods. (8) The adhesion strength was measured at the same three points as in Example 1, and the peel strength was 2.5 to 2.4 kg / cm. (9) A circuit or connector was formed on the substrate using photolithography, followed by a 0.2 μm Pd plating layer, and then a 0.01 μm Au layer was further applied on top of it. Finally, SiC-type power transistors were actually installed. For comparison purposes, the fusion layer of the present invention is not formed, and the other processes are exactly the same as those in this embodiment. Even with such manufacturing, the peel strength measured at 3 points is 0.1 to 0.01 kg / cm, which means it is not tightly bonded at all. It can be confirmed that this embodiment can surprisingly improve the adhesion.

[0068] Example 3 An AlN substrate was used as the bonding substrate. (1) Using an AlN substrate (manufactured by Tokuyama Corporation, trade name: SHAPAL), the substrate was degreased, pickled, etched, and then dried using conventional methods. (2) As an anchoring agent, water was added to 50g of BN particles of 0.5-1.5μm, 50g of sodium molybdate, 10g of titanium sulfate, and 50g of kaolin to make 1L, and stirred for 5 hours to prepare a welding agent for forming a weld layer. (3) A dry film was applied to the AlN board of (1), and openings were made in the parts that become the circuit part and the connector part using photolithography. (4) The welding agent of (2) was sprayed so that the welding agent only remained in the opening, and then it was allowed to dry naturally. (5) The film was heated at 200°C for 1 hour in an electric furnace to remove the flux remaining on the dry film, and then heated at 1100°C for 3 hours. BN particles were welded only at the openings. (6) In order to obtain a primary metal layer, a 3 μm non-electrolytic copper plating layer was applied after sensitizing and activating agent treatment. At this time, a copper plating layer was deposited on the entire surface. (7) In order to leave only the copper plating in the opening, the entire surface is covered with a tape. When it is peeled off, the copper plating is peeled off because the parts outside the opening where the anchor is not fixed are not tightly attached, and only the plating remains in the opening. (8) In order to obtain the secondary metal layer, a non-electrolytic copper plating layer with a thickness of 20 μm was applied. (9) It was subjected to heat treatment at 450°C for 30 minutes in the atmosphere. (10) The adhesion strength was measured at 3 points, and the peel strength was 2.6 to 2.5 kg / cm. For comparison, the peel strength of AlN plates in areas without anchor formations was measured at 3 points and ranged from 0.1 to 0.05 kg / cm.

[0069] Example 4 Sapphire (99.99% Al2O3) was used as the bonding substrate. (1) The sapphire substrate was degreased, etched and dried using conventional methods. (2) As an anchoring agent, 30g of Pyrex glass powder with a particle size of 0.3-1.5μm, 50g of ferrous ammonium sulfate, 20g of MoO3, 20g of H3BO3, 1g of AgNO3, and 5g of silane coupling agent A-1100 were added to make 1L of the mixture. The mixture was stirred for 5 hours to prepare the welding agent for forming the weld layer. (3) The flux prepared in (2) is applied to the sapphire substrate of (1) by spraying. (4) After natural drying, the glass particles were heated at 700°C for 2 hours and then at 1100°C for 2 hours. The glass particles were then fused onto the sapphire substrate. (5) In order to obtain a primary metal layer, a 0.5 μm Ti and a 2 μm Cu layer are stacked and covered on the entire surface by ion plating. (6) Subsequently, a 30 μm thick copper sulfate plating layer was applied to obtain a secondary metal layer. The adhesion strength was measured at 3 points, and the peel strength was 1.8–1.7 kg / cm. For comparison purposes, the welding process of the anchor formation in this embodiment has been omitted, while the other processes are exactly the same as those in this embodiment. Even with this manufacturing process, the peel strength measured at 3 points is only 0.3 to 0.1 kg / cm, making it unsuitable for use as a substrate for actual mounting of electronic components.

[0070] Example 5 Commercially available SiC boards were used as the bonding substrate. (1) The SiC board was degreased and etched using conventional methods and then dried. (2) As an anchoring agent, 30g of SiC particles with a particle size of 0.3 to 1.5μm sold on the market, 50g of porcelain glaze (ceramic glaze: SK-12), 20g of AgNO3, 10g of EDTA-Cu, 5g of titanium sulfate, and 20g of B2O3 were mixed with water to make 1L, and stirred for 5 hours to prepare a welding agent containing the anchoring agent. (3) The welding agent was uniformly applied to the SiC plate of (1) by spraying. After that, it was naturally dried for 10 hours. (4) It was heated at 1300℃ for 3 hours using an electric furnace. (5) SiC particles are uniformly fused onto the SiC plate. (6) In order to obtain a primary metal layer, a 1.0-1.5 μm non-electrolytic Ni-B coating was applied to the entire surface after treatment with sensitizers and activators using conventional methods. (7) A dry film was applied and processed using photolithography so that only the circuit or connector part became an opening. Then, a copper sulfate plating bath was used to apply a 30μm plating layer to the connector head and circuit part, thereby forming a secondary metal layer. (8) After the dry film is peeled off, the parts other than the circuit and connectors are removed by rapid etching. This is the so-called circuit formation method using the SAP (semi-additive process). The adhesion strength of the circuit, measured at 3 points, has a peel strength of 1.9–1.8 kg / cm. For comparison purposes, the process of fixing the anchor forming involved in this embodiment has been omitted, while the other processes are exactly the same as those in this embodiment. Even with such manufacturing, the peel strength measured at 3 points is only 0.3 to 0.1 kg / cm, which is not a strength that can be used in practice.

[0071] Example 6 WC boards, which are commercially available, were used as the bonding substrate. (1) The WC board was degreased and etched using conventional methods and then dried. (2) As an anchoring agent, water was added to 30g of SiC particles with a particle size of 0.5-1.5μm, 10g of silane coupling agent A-1100, 50g of vanadium sulfate, 50g of commercially available porcelain enamel (SK-9), and 10g of water glass to make 1L of the mixture. The mixture was stirred for 5 hours to prepare a welding agent containing the anchoring agent. (3) The welding agent is uniformly applied to the WC plate of (1) by spin coating. After that, it was left to air dry for 10 hours. (4) It was heated at 1200℃ for 3 hours using an electric furnace. (5) SiC particles are uniformly fused onto the WC plate. (6) As a primary metal layer, 1.0 μm of copper was covered by sputtering. Subsequently, a 50μm copper (secondary metal layer) plating was applied by copper electroplating. (7) The heat treatment was carried out at 400°C for 30 minutes in an N2+H2 environment. (8) The adhesion strength was measured at 3 points, and the peel strength was 2.9 to 2.4 kg / cm. For comparison, the adhesion strength without the treatment of this embodiment was measured at 3 points, and the peel strength was about 0.1 to 0.03 kg / cm. In the transparent tape test, peeling occurred easily.

[0072] Example 7 Commercially available AlN boards (SHAPAL) were used as the bonding substrate. (1) The AlN plate was degreased, etched and dried using conventional methods. (2) As an anchoring agent, water was added to 60g of Ni fine powder with an average particle size of 1.5μm, 50g of MoO3, 10g of B2O3, and 50g of silane coupling agent (A-1100) to make 1L. A welding agent containing anchor formations was prepared by mixing for 5 hours to form the weld layer. (3) A dry film was applied to the entire surface and processed using photolithography so that only the circuit part and the connector part became the opening part. (4) The welding agent of (2) was applied only to the opening. (5) After natural drying, it was heated at 1100℃ for 2 hours in an electric furnace. (6) After treatment with sensitizer and activator, a 3μm non-electrolytic copper plating layer was applied to the entire surface. (7) Photolithography was performed using the same process as (3) to make the circuit part and the connector part into opening parts. (8) A 20μm copper plating layer was applied to only the connector and circuit section by electroplating, and a Ni-Pd-Au plating layer was further applied on top of it. After stripping the resist, the thinner copper plating film existing outside the circuit section and connector section was stripped (SAP method), and a plating substrate with only the connector section or circuit section remaining was made, and the power transistor was actually installed at the connector section. (9) Adhesion strength is 2.7-2.5 kg / cm and peel strength is 2.7-2.5 kg / cm. For comparison, the adhesion strength of the substrate without anchor formation is 0.1 to 0.01 kg / cm, and the peel strength is 0.1 to 0.01 kg / cm.

[0073] Example 8 Commercially available SiC substrates were used as bonding substrates. (1) The SiC substrate was degreased, etched and dried using conventional methods. (2) As an anchoring agent, 1L of water was prepared by adding water to 60g of SiC fiber with a diameter of 1.0μm and a length of 4-5μm, 50g of water glass, 50g of ammonium molybdate, 50g of vanadium oxide, and 5g of boric acid. The mixture was stirred for 3 hours to prepare a welding agent for forming the welding layer. (3) The welding agent is applied to the SiC plate of (1) by spraying. (4) After natural drying, it was heated at 1100°C for 3 hours. The SiC fibers were fixed by being stacked in a mesh-like manner. (5) A 30 μm copper sulfate plating layer was applied after a 3 μm non-electrolytic copper plating layer using a known method. The adhesion strength was measured at 3 points, and the peel strength was 2.8–2.6 kg / cm. On the other hand, the adhesion strength of the substrate not coated with the welding agent of the present invention was measured at 3 points, and the peel strength was 0.1 to 0.01 kg / cm.

[0074] In the above embodiments 1 to 8, compared with the case where the intermediate cover film of the present invention, i.e. the welding layer, is not formed (i.e., in the case of the conventional coating method), the adhesion strength of the present invention is several times to tens of times stronger, and the deviation of its strength can be confirmed to be extremely small.

[0075] Example 9 The adhesion strength and its deviation were compared with those of existing methods using an Al2O3 substrate with a thickness of 100mm×80mm×0.3mm. Existing methods involve immersing the surface in a molten salt with a strong alkali, etching the surface, and then applying a coating. The test method involved fabricating a 2mm × 2mm connector on an Al2O3 substrate and measuring the adhesion strength (tensile strength) by soldering the metal wire and then stretching it in the vertical direction. The primary metal layer was coated with a 0.5 μm electroless Cu plating, the secondary metal layer was coated with a 40 μm Cu plating, and a 0.1 μm electroless Au plating was applied on the Cu to improve solderability. The number of measurements was 10 locations. The results of the tensile tests are shown in Table 1.

[0076] Table 1 This embodiment 4.3 4.8 4.0 3.7 4.4 4.2 4.0 3.9 4.4 4.2 Comparative example 3.8 5.2 1.0 4.1 3.0 3.6 2.2 3.1 0.8 4.2

[0077] As can be seen from the results in Table 1, the tensile strength of this embodiment (using the same method as in Example 3) is high, and its deviation is extremely small. On the other hand, it is known that although the comparative examples of existing methods also have fairly high strength, their deviations are large. It can be confirmed that the present invention has greater strength and extremely small deviation compared to the prior art.

[0078] Examples 10-29, when the combination of ceramic substrate, anchoring material, and welding composition is changed, are shown in Tables 2-21.

[0079] In the table, comparative examples represent the peel strength of existing methods when no weld binder is applied. In the table, the peel strength is the same in Examples 1 to 8. The results of the present invention and the comparative examples are measured at 3 points.

[0080] In Examples 10-29, the pretreatment of the bonding substrate and the application of the welding agent were performed using the same methods as in Examples 1-8. Furthermore, after the secondary coating was applied, both these examples and the comparative examples underwent heat treatment at 400°C for 30 minutes in a N2 environment, after which the peel strength was measured.

[0081] Example 10 The results are shown in Table 2. Table 2

[0082] Example 11 The results are shown in Table 3. Table 3

[0083] Example 12 The results are shown in Table 4. Table 4

[0084] Example 13 The results are shown in Table 5. Table 5

[0085] Example 14 The results are shown in Table 6. Table 6

[0086] Example 15 The results are shown in Table 7. Table 7

[0087] Example 16 The results are shown in Table 8. Table 8

[0088] Example 17 The results are shown in Table 9. Table 9

[0089] Example 18 The results are shown in Table 10. Table 10

[0090] Example 19 The results are shown in Table 11. Table 11

[0091] Example 20 The results are shown in Table 12. Table 12

[0092] Example 21 The results are shown in Table 13. Table 13

[0093] Example 22 The results are shown in Table 14. Table 14

[0094] Example 23 The results are shown in Table 15. Table 15

[0095] Example 24 The results are shown in Table 16. Table 16

[0096] Example 25 The results are shown in Table 17. Table 17

[0097] Example 26 The results are shown in Table 18. Table 18

[0098] Example 27 The results are shown in Table 19. Table 19

[0099] Example 28 The results are shown in Table 20. Table 20

[0100] Example 29 The results are shown in Table 21. Table 21

[0101] In the examples 10 to 29 shown in Tables 2 to 21, the adhesion strength was 2.9 to 2.0 kg / cm. On the other hand, when no weld binder was applied (comparative example), the peel strength was 1.0 to 0.01 kg / cm. The intensity of this embodiment is significantly higher than that of the comparative example, and the deviation of its data is also very small. As a substrate for power semiconductors, a peel strength of 1.0 kg / cm or higher is required. However, in the comparative example, although there are parts with a maximum strength of 1 kg in the same test piece, the strength is lower in other parts, and the condition cannot be met in all areas. It has been determined that the present invention can obtain a strength more than twice the minimum necessary strength, with a small deviation from the required strength. Furthermore, even if the composition of the welding agent is changed, a stable strength can be obtained, thus enabling a highly reliable bond.

[0102] Industrial availability Its biggest applications are heat sinks for power transistors or LEDs, parts for electric vehicles, fuel cells, etc., and it is expected to have significant growth potential.

Claims

1. A bonding body for a substrate and a metal layer, wherein the metal layer is bonded to the bonding surface of the substrate via an intermediate cover film, characterized in that, The bonding substrate is made of ceramic. The intermediate layer covering film is a glassy oxide formed by melting a compound of one or more metal components. Anchor-forming elements are dispersed and embedded in the intermediate cover film, while the intermediate cover film is fused to the bonding surface of the bonding substrate. The anchors bond the metal layers through an anchoring effect. A portion of the embedded anchor protrudes outward from the intermediate cover membrane while being fused to it. The metal layer is constructed such that a secondary metal layer is formed on a primary metal layer formed on an intermediate cover film. The diameter of the anchor formation is 0.1–30 μm. The anchor morphology is spherical, angular, or polygonal in shape, and is a three-dimensional fibrous or mesh-like structure formed by the combination of dispersed and embedded anchor morphologies. The primary metal layer fills the gaps between the anchor formations that protrude outward from the surface of the intermediate cover film, surrounds the anchor formation protrusions, and is bonded to the surface of the intermediate cover film.

2. The bonding body of the bonding substrate and the metal layer according to claim 1, characterized in that the anchoring material is one or a mixture of two or more of the following: oxide powder, carbide powder, nitride powder, boride powder, silicide powder, diatomaceous earth powder, silica powder, glass powder, diamond powder, DLC powder, ceramic powder, porcelain powder, silica fiber powder, ceramic fiber, mica powder, graphite powder, kaolin powder, fiber or metal whiskers.

3. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The bonding substrate can be any one of Al2O3, AlN, Si3N4, BN, SiC, ZrC, WC, DLC, diamond, silicon wafer, sapphire, ceramics, porcelain, GaC, GaAs, GaN, GaO, LED, or graphite.

4. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The shape of the bonding substrate can be any of the following: plate-shaped, columnar, spherical, cylindrical, or rod-shaped.

5. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The covering metal of the primary metal layer is composed of one or more metals.

6. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The thickness of the primary metal layer is 0.001–10 μm.

7. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The covering metal of the secondary metal layer is a layer of one metal or two or more metals, or an alloy of two or more metals.

8. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, The thickness of the secondary metal layer is 0.1 μm to 10 cm.

9. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, Circuit portions and / or connector portions are formed on a ceramic substrate that serves as the bonding substrate.

10. The joint between the bonding substrate and the metal layer according to claim 9, characterized in that, The secondary metal layer surface of the circuit section and / or connector section is coated with any one of Ni, Sn, Pd, Ag, Au, Pt, Pb, Ni / Pd / Au, Ni / Sn, Ni-Sn-Ag-Cu, Sn-Bi or Sn-Cu.

11. The joint between the bonding substrate and the metal layer according to claim 1 or 2, characterized in that, Electronic components are mounted on the metal layer.

Citation Information

Patent Citations

  • Ceramic multilayer circuit board

    JP1986058296A

  • Manufacture of ceramic multilayer interconnection circuit board

    JP1986170094A

  • Ceramic wiring board

    JP1989181499A

  • Production of liquid crystal display device

    JP1991002833A

  • Method of direct bonding metals to non-metallic substrates

    US3766634A